Self-Affirmation and Identity-Driven Political Behavior. Issue 2 (8th February 2022) - Lyons, Benjamin A.; Farhart, Christina E.; Hall, Michael P.; Kotcher, John; Levendusky, Matthew; Miller, Joanne M.; Nyhan, Brendan; Raimi, Kaitlin T.; Reifler, Jason; Saunders, Kyle L.; Skytte, Rasmus; Zhao, Xiaoquan
Abstract: Psychological attachment to political parties can bias people's attitudes, beliefs, and group evaluations. Studies from psychology suggest that self-affirmation theory may ameliorate this problem in the domain of politics on a variety of outcome measures. We report a series of studies conducted by separate research teams that examine whether a self-affirmation intervention affects a variety of outcomes, including political or policy attitudes, factual beliefs, conspiracy beliefs, affective polarization, and evaluations of news sources. The different research teams use a variety of self-affirmation interventions, research designs, and outcomes. Despite these differences, the research teams consistently find that self-affirmation treatments have little effect. These findings suggest considerable caution is warranted for researchers who wish to apply the self-affirmation framework to studies that investigate political attitudes and beliefs. By presenting the "null results" of separate research teams, we hope to spark a discussion about whether and how the self-affirmation paradigm should be applied to political topics.